Hubungan Motivasi Terhadap Kinerja Kader Pada Program Gerakan Menekan Angka Kematian Ibu Dan Bayi (Gemakiba) Di Kelurahan Sukorame Kota Kediri Wilayah Kerja Puskesmas Sukorame - Triatmi Andri Yanuarini; R. Maria Low Dhika Febri Wulandari; Suwoyo Suwoyo (coba, 2018)
The indicator that can be used to measure of status health mother in certain region such as using number of maternal mortality (Angka Kematian Ibu / AKI). AKI is one of indicator that sensitive about quality and an access to facility health service. One of factor that contributed to maternal mortality is factors that complicate of process handling emergency such as TIGA TERLAMBAT. It used to press AKI, the government made programs. The program is Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) and Kediri was held program Gerakan Menekan Angka Kematian Ibu dan Bayi (GEMAKIBA). The aim of this research is to know the relationship of motivation performance cadre at GEMAKIBA’s program at Sukorame district Kediri city region performance of clinic Sukorame. The research design is survey analytic. The approach is cross sectional, the population is 45 persons of cadre. The sampling uses simple random sampling with 41 respondences of cadre that fulfil of inclusive criteria. The instrument used questioner to assess of motivation, checklist to assess of performance and recapitulation sheet to make a note the result of data. Then the data was analyzed with correlation spearman rank that showed there is a relathionship between motivation and performance cadre at GEMAKIBA’s program. Based on the result of the research above it should be became a material to maintain and enhance motivation for more comprehensive program’s outcomes.